A quantitative study on the effects of an interactive multimodal application to promote students' learning motivation and comprehension in studying Tang poetry - Chen, Chuang; Jamiat, Nurullizam (Frontiers in Psychology, 2023)
Studying China’s Tang poetry is a crucially integrated part of the language curriculum in primary schools because it is an important part of its cultural heritage and classical literature. However, due to the fact that Tang poetry is written in classical Chinese, which is quite different from modern Chinese Mandarin, and the complex categories of this poetry style, learning Tang poetry can be a challenging experience for many students. To address this problem, this study developed an interactive multimodal application based on the cognitive-affective theory of learning with media to learn Tang poetry in an interactive way. In order to assess the effectiveness of this method, a pretest-posttest control group experiment was conducted. The experiment included eighty third-grade students randomly and equally divided into experimental and control groups from an elementary school in Xinzheng, Henan Province, to test (1) whether the interactive multimodal application improves students’ reading comprehension of Tang poetry and (2) whether the application enhances students’ intrinsic and/or extrinsic motivation in learning Tang poetry. A multimodal interactive application was used by the experimental group to learn Tang poetry, while the control group used a traditional classroom method. According to the study's findings, it was found that students' intrinsic motivation and comprehension of Tang poetry improved through the use of the interactive multimodal application mode.